Surgical management of penile mondor’s disease: Case report and brief review of literature - Gahlawat, Sumit; Gupta, Deepanshu; Kumar, Anuj; Sood, Rajeev (Indian Journal of Case Reports, 2022)
Penile Mondor’s disease (PMD) is a rare condition characterized by thrombosis of superficial dorsal vein of the penis. PMD is usuallycaused due to vigorous sex or repeated trauma to the penis leading to painful swelling of the penis. Most of the patients improvegradually on conservative treatment. Very rarely cord like lesion persists and causes painful erection and intercourse, meriting surgicalmanagement. Here, we report the case of a traumatic Thrombophlebitis of Superficial Dorsal Vein of Penis managed surgically alongwith a brief explanation of the surgical technique. Color Doppler was helpful in delineating the whole extent of thrombus in thevein. Excision of the whole length of the thrombosed vein was done. Abstinence from sex was advised for six weeks and the patientimproved symptomatically.